Selection of endemic nonpathogenic endophytic Fusarium oxysporum from bean roots and rhizosphere competent fluorescent Pseudomonas species to suppress Fusarium-yellow of beans - Dhingra, Onkar D.; Coelho-Netto, Rosalee A.; Rodrigues, Fabrício Á.; Silva Jr., Geraldo J. (Biological Control, 2006)
A less resource intensive procedure was used to select an endophytic non-pathogenic isolate of Fusarium oxysporum (NPFo) and an antibiotic producing rhizosphere/rhizoplane (RS-RP) competent fluorescent pseudomonad to suppress Fusarium yellow (F. oxysporum (Schlecht) f. sp. phaseoli Kendrick and Snyder) of bean (Phaseolus vulgaris L.). Using the combined criteria of in vitro and in planta competitiveness resulted in selection of three isolates for determination of their disease suppressing attributes. Several isolates of fluorescent pseudomonads obtained from RS-RP and internal root tissues of bean were tested for antibiosis in vitro. The isolates producing large inhibition zones were selected to determine RS-RP competence through seed treatment. The three most competent isolates were tested for their capacity to reduce root colonization by the pathogen, which resulted in the selection of only one isolate, identified as Pseudomonas putida (Trevisan) Migula biotype A. The NPFo isolates Fo10 and Fo6 endophytically occupied about 80% of the root length compared to only 60% by the isolate Fo16. Mixing chlamydospores of Fo10 in non-sterile field soil, reduced RS-RP and internal root colonization by the pathogen by 95 and 89%, respectively. In the greenhouse trial, mixing chlamydospores of either of the three NPFo isolates, the area under the chlorophyll retention curve (AUCRC) increased significantly with Fo10 compared to Fo6 or F16, over the positive control. The grain yield/plants from Fo10 treated soil was 177 or 291% higher than from Fo6-soil or positive control, respectively, but remained 50% lower than in pathogen-free negative control soil. In the field plots with pathogen ID of 850 ± 150/g soil, mixing chlamydospores of Fo10 (4250 ± 113/g), increased AUCRC and grain yield by about 100% over the control. However, if the bean seeds were treated with P. putida, the grain yield increased by 211% without further increase in AUCRC. The suppressive effect of Fo10 on disease development appeared to be related to its high saprophytic competitiveness with the pathogen in the soil matrix, which resulted in lower ID in the root zone, and parasitic competitiveness by reducing the availability of infection sites and internal root colonization by the pathogen. Seed treatment with P. putida provided additional protection in the root zone.
Keywords: Biocontrol; Chlorophyll retention curve; Disease suppression; Fusarium oxysporum f. sp. phaseoli; Non-pathogenic Fusarium oxysporum; Parasitic competition; Pseudomonas putida Saprophytic competition; Soilborne pathogen; Vascular wilt